Determinants of pedagogical innovation in higher education: Initial exploration of factors for a varied and active pedagogy - Girouard-Gagné, Myriam; Deschênes, Noémie; Bégin-Caouette, Olivier; Jones, Glen Alan; Karram Stephenson, Grace; Metcalfe, Amy (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2025)
A learner-centred approach involving active teaching methods seems to be encouraged in higher education to respond to the changing context. However, no quantitative study has been carried out to understand the factors determining varied and active teaching practices among professors, which this article proposes to do. Descriptive statistical analyses and a logistic regression were performed using data collected from 2968 Canadian university professors. It seems that professors who use a more varied pedagogy have had training in pedagogy, prefer teaching, work more hours per week, carry out formal self-evaluations of their teaching, or practice in the fields of natural sciences and health.